Finite Element Analysis Of Pull-Out Performance Of Bone Screw - Tan, Yong Quan (Universiti Sains Malaysia, 2022)
In orthopaedic surgery, bone screws were frequently used in open reduction internal fixation (ORIF) to keep the broken bones in place by screw’s compression force to cure the bone fracture. It was critical to thoroughly examine its parameters, especially the pull-out strength, to accelerate bone healing and minimise additional injury. Previous studies focused on bone properties, screw design, and insertion techniques of bone screw, through experimental or computational approach. The insertion angle of bone screw was often mentioned as one of the potential parameters influencing pull out strength of the bone screw, yet it had received comparatively little attention and was not the key element on any research particularly with numerical approach. The purpose of this project was to numerically examine the effect of insertion angle of bone screw on its axial pull-out strength. The stress-strain field after the screw insertion and residual field after the screw pull-out were examined and analysed. 3-dimensional finite element (3D FE) model of a cortical bone and solid rigid polyurethane foam block were modelled and were computational simulated for pull-out test complying ASTM F543 standards. The total deformation, equivalent elastic strain, and equivalent stress were evaluated from the simulation results for both the screw insertion and pull-out. The pull-out force of the screw inserted into synthetic human bone was measured. The study concluded that the increase in bone screw insertion angle will reduce the pull-out strength. The stress-strain distribution was concentrated at screw-block contact zone after the insertion, providing better fixation to the screw despite having lesser contact volume at high insertion angle, leading to insignificant improvement. The residual field of the foam block after the bone screw was pulled out promoted bone cure.